ANALISA PENGARUH LOG TRANSAKSI PADA SISTEM KOMPUTER MENGGUNAKAN ALGORITMA RECOVERY BERBASIS LOG - Sianturi, Fricles Ariwisanto (Journal of Computer Networks, Architecture and High Performance Computing, 2019)
This study aims to melakukakan analysis of the effect of the transaction log on a computer based system either on a single system tired, and two tiered through simulated transactions bank system with technology client / server to get a log of transactions on the database system Microsoft Windows SQL Server 2008 R2 management studio a data base. Methods or algorithms are used to analyze the transaction log on the system used is a log-based recovery algorithm.The results based on the analysis, showed that the use of query local database and query the database using sotere procedure to get the transaction log for troubleshooting transactions on the database system via a user interface is built to help job database administrator (DBA), much more good compared with conventional systems. Based on the experiments that the log of transactions to be controlled, in-undo, Re-do, or Rolled-Back, even deleted if no longer required automatically to maintain the scalability of computer users in the future, by setting the growth of a standard database from 10% to > 32%, and the establishment of a maintenance schedule to ensure that the reserve database is always available and up to date.